Understanding Emotions in Early Europe - Champion, Michael; Lynch, Andrew (Brepols, 2015)
This book investigates how medieval and early modern Europeans constructed, understood, and articulated emotions. The essays trace concurrent lines of influence that shaped post-Classical understandings of emotions, through overlapping philosophical, rhetorical, and theological discourses. They show the effects of developments in genre and literary, aesthetic, and cognitive theories on depictions of psychological and embodied emotion in literature. They map the deeply embedded emotive content inherent in rituals, formal documents, daily conversation, communal practice, and cultural memory. The contributors focus on the mediation and interpretation of pre-modern emotional experience in cultural structures and institutions - customs, laws, courts, religious foundations - as well as in philosophical, literary, and aesthetic traditions. The volume thus represents a conspectus of contemporary interpretative strategies, displaying close connections between disciplinary and interdisciplinary critical practices drawn from historical studies, literature, anthropology and archaeology, philosophy and theology, cognitive science, psychology, religious studies, and gender studies. The essays stretch from classical and indigenous cultures to the contemporary West, embracing numerous national and linguistic groups. They illuminate the complex potential of medieval and early modern emotions <span class=